1986
DOI: 10.1577/1548-8640(1986)48<95:iwehal>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Increased Walleye Egg Hatch and Larval Survival after Protease Treatment of Eggs

Abstract: Various techniques for eliminating the clumping of newly spawned walleye eggs (Stizostedion vitreum) were evaluated by measuring hatch, growth, and survival. Percent hatch was highest (83%) in egg groups water hardened in 0.01% protease solution. Other water-hardening techniques tested were: (1) continuous stirring; (2) 250 mg/L tannic acid solution; and (3) bentonire clay suspension. Low hatching percentages for eggs continuously stirred or treated with bentonire were attributed to fungus. Fungus was minimal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 9 publications
1
25
1
Order By: Relevance
“…Krise et al (1986) pointed out that the adhesive layer surrounding the chorion is particularly susceptible to viral, fungal, and bacterial pathogens and that removal of this can significantly reduce the development of such pathogens. Furthermore, routine disinfection and removal of dead eggs during egg incubation are important for improved biosecurity, both of which can be made easier and more effective by incubating eggs in suspension.…”
Section: Discussionmentioning
confidence: 99%
“…Krise et al (1986) pointed out that the adhesive layer surrounding the chorion is particularly susceptible to viral, fungal, and bacterial pathogens and that removal of this can significantly reduce the development of such pathogens. Furthermore, routine disinfection and removal of dead eggs during egg incubation are important for improved biosecurity, both of which can be made easier and more effective by incubating eggs in suspension.…”
Section: Discussionmentioning
confidence: 99%
“…It has been used as antifungal treatment in egg incubation of different freshwater fish species such as: Clarias garepinus, Cyprinus carpio, Oncorhynchus mykiss and Ictalurus punctatus (Marking et al, 1994;Froelich and Engelhardt, 1996;Schreier et al, 1996;Weirich and Tiersch, 1997;Khodabandeh and Abtahi, 2006;Rasowo et al, 2007). Increased salinity was also applied in intensive culture for increased survival and osmoregulatory of percid larvae (Krise et al, 1986;Guo et al, 1993;Bein and Ribi, 1994) and for control of fish diseases in intensive freshwater finfish culture (Mifsud and Rowland, 2008). Weirich and Tiersch (1997) found positive effect of increased salinity (application of 1 g NaCl·L −1 ) in hatchery water on the hatching rate in I. punctatus.…”
Section: Discussionmentioning
confidence: 99%
“…In the Gulf Acipenser eggs, the use of fullers and clay decreased the duration of egg de-adhesion procedure to half (Elizabeth, 2001). In white sturgeon Acipenser transmontanus, a combination of urea/salt or sodium sulfite accompanying tannic acid decreased considerably the duration of egg deadhesion procedure (Krise et al, 1986). Demska-Zake et al (2005) observed a significant decrease in the duration of egg de-adhesion of walleye, pike perch (Sander lucioperca) when he used tannic acid.…”
Section: Discussionmentioning
confidence: 99%